Creative template-dependent synthesis by human polymerase mu - Moon, Andrea F. (Proc Natl Acad Sci U S A, 2015)
Among the many proteins used to repair DNA double-strand breaks by nonhomologous end joining (NHEJ) are two related family X DNA polymerases, Pol λ and Pol µ. Which of these two polymerases is preferentially used for filling DNA gaps during NHEJ partly depends on sequence complementarity at the break, with Pol λ and Pol µ repairing complementary and noncomplementary ends, respectively. To better understand these substrate preferences, we present crystal structures of Pol µ on a 2-nt gapped DNA substrate, representing three steps of the catalytic cycle. In striking contrast to Pol λ, Pol µ “skips” the first available template nucleotide, instead using the template base at the 5′ end of the gap to direct nucleotide binding and incorporation. This remarkable divergence from canonical 3′-end gap filling is consistent with data on end-joining substrate specificity in cells, and provides insights into polymerase substrate choices during NHEJ.